Genomic engineering in Rhizobium etli: implementation and evaluation of systems based on dCas9 - Bellahsen, Oussama; Díaz-Méndez, Rafael; Romero, David (Frontiers in Microbiology, 2025)
CRISPR-Cas9 is a powerful tool for gene editing and regulation, facilitating the analysis of gene function. In this study, we developed a robust CRISPR interference (CRISPRi) system to precisely modulate gene expression in the bacterium Rhizobium etli, the nitrogen-fixing symbiont of the common bean. The system is based on two compatible plasmids (pBBR1MCS2-dCas9 and pRhigRNA containing specific guide RNAs). Introduction of both plasmids in R. etli led to significant repression of four target genes [DsRedexpress, recA, thiC (on the thiCOSGE operon) and rdsA] depending on the guide RNA used. By employing different guide RNAs at various target sites, we obtained up to 90% gene repression. Importantly, neither significant secondary effects on growth nor toxicity were observed upon expression of dCas9, either alone or in co-expression with the guide RNAs. This system can be utilized for further investigations on the function of essential genes in R. etli, or it can be integrated with other gene expression elements or gene editing tools, such as base editors for advanced genome engineering in Rhizobiales.